ANALYSIS OF BUBBLE SORT AND INSERTION SORT ALGORITHM ON MEMORY EFFICIENCY USING DATA MINING APPROACH - Iskandar, Iqbal Dzulfiqar; Amirulloh, Imam; Pertiwi, Melisa Winda; Kusmira, Mira; Hikmah, Agung Baitul; Supriadi, Deddy (Jurnal Pilar Nusa Mandiri, 2020)
Sorting algorithm in the computational process makes it easy for users when the data sorting process because the data is sorted by the process quickly and automatically. In addition to speed in sorting data, memory efficiency must also be considered. In this research, a retesting of two sorting methods is conducted, namely the bubble sort method and the insertion sort method based on the comparison of two programming languages, Java with Visual Basic 2010 using the decision tree method. This research aims to find out which algorithm has lower memory consumption in the sorting process using Java or Visual Basic 2010. The results of the comparison show, in Visual Basic 2010. insertion sort algorithm which has the lowest average memory consumption of 4.3243KB for .vb extensions and 2.0145KB for .exe extensions. while the bubble sort method with a consumption amount of 4.4358KB for the .vb extension and 2.0352 for extension.exe. Furthermore, if you use the Java programming language. So the bubble sort method still consumes the highest average memory, which is 546,242KB for the .jar extension and 4,337KB for the .exe extension, whereas from the insertion sort method, which has a low average memory consumption of 543,578 KB for extension .jar, and 4,381KB for extension .exe.